Characterization of the [2Fe-2S] cluster of the Escherichia coli transcription factor IscR() - Fleischhacker, Angela S. (2012)
IscR is a Fe-S cluster-containing transcription factor involved in a homeostatic mechanism that controls Fe-S cluster biogenesis in Escherichia coli. Although IscR has been proposed to act as a sensor of the cellular demands for Fe-S cluster biogenesis, the mechanism by which IscR performs this function is not known. In this study, we investigated the biochemical properties of the Fe-S cluster of IscR to gain insight into the proposed sensing activity. Mössbauer studies revealed that IscR contains predominantly a reduced [2Fe-2S](1+) cluster in vivo. However, upon anaerobic isolation of IscR some clusters became oxidized to the [2Fe-2S](2+) form. Cluster oxidation did not, however, alter the affinity of IscR for its binding site within the iscR promoter in vitro, indicating that cluster oxidation state is not important for regulation of DNA binding. Furthermore, characterization of anaerobically isolated IscR using resonance Raman, Mössbauer, and NMR spectroscopies leads to the proposal that the [2Fe-2S] cluster does not have full cysteinyl ligation. Mutagenesis studies indicate that, in addition to the three previously identified cysteine residues (Cys92, Cys98, and Cys104), the highly conserved residue His107 is essential for cluster ligation. Thus, these data suggest that IscR binds the cluster with an atypical ligation scheme of three cysteines and one histidine, a feature that may be relevant to the proposed function of IscR as a sensor of cellular Fe-S cluster status.